How Girl Scout Innovators Charmed Obama's White House: The Politics of Advocacy for Young Women in STEM. - Bix, Amy Sue (Transactions of the American Philosophical Society, 2025)
The article discusses the evolution of advocacy for young women's participation in STEM (science, technology, engineering, and mathematics) during the Obama and Trump administrations, highlighting significant events and initiatives. It details how President Obama emphasized diversity and inclusion in STEM through various White House Science Fairs, where young Girl Scouts showcased innovative projects, capturing media attention and presidential support. The article also notes the shift in focus during the Trump administration, where advocacy continued but was framed more around workforce needs and corporate partnerships, despite cuts to educational funding. Overall, the piece illustrates how girls' STEM advocacy has become a mainstream political and cultural issue, supported by both governmental and corporate entities, while acknowledging ongoing challenges in achieving true equity in STEM fields.